(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This article analyzes “sentimental embezzlement” based on the bills currently in the process of being drafted, which seek to typify it in the Brazilian legal system. This crime occurs when an individual deceives the victim with fraudulent promises of affection, leading them to transfer assets under the belief of a genuine relationship. This practice results not only in financial losses, but also in psychological damage, making it a relevant issue for the law. Despite the lack of a specific definition, the subject generates debate about its characterization as a crime and its civil and criminal implications. The concept is similar to traditional embezzlement, provided for in article 171 of the Penal Code, but subjectivity and the difficulty of proving it make it difficult to apply. The article investigates the viability of a legal framework for sentimental fraud in Brazil, considering its relationship with criminal and civil law. The methodology used was bibliographical research, analysis of legal doctrines and scientific articles on emotional fraud. The results indicate that, although it is possible to classify it under Article 171, the lack of express legal provision makes it difficult to apply. In addition, there is growing recognition of civil liability, allowing for compensation. The conclusion is that sentimental fraud presents legal and evidential challenges, requiring debate on its criminal classification and protection mechanisms for victims.